Analysis of dynamic characteristic and structure optimisation for hybrid machine tool. (14th July 2009) - Zhu, Chunxia; Zhu, Lida; Wang, Jianrong; Su, Cong; , Wanshan Wang
A new method that the exciting vibration test is simulated to analyse the dynamic characteristic of hybrid machine tool is proposed. The principle of exciting vibration test on dynamic characteristic is researched, and the skeleton and design process of swept sine vibration test is also given. In order to obtain accurate simulation results, the rigid?flexible coupling system model of hybrid machine tool is built in ADAMS software, which forms the exciting vibration simulation model. The exciting force is loaded on the coupling vibration system and brings displacement response, and then the curves of displacement response are obtained. According to the simulation results, the weak parts are effectively optimised and the simulation is carried out again on the optimised structure; then the simulation results are ideal and the deformation of weak parts is also reduced. Therefore, the simulation method can effectively improve the dynamic characteristic of hybrid machine tool.